Development of a Web-Based Payroll Information System Using Extreme Programming - Dharsika, I Gde Eka; Mahendra, Muhammad Rian Asrizal; Satwam, I Ketut Sassu Budi (PT.KARYA GEMAH RIPAH, 2025)
Arj88 Store operates in the clothing retail sector and currently relies on spreadsheet-based tools for employee payroll processing. This approach requires repetitive verification, is time-consuming, and increases the risk of errors, particularly in managing salary components such as benefits, deductions, and payroll-related reports. To address these limitations, this study adopts the Extreme Programming (XP) methodology due to its flexibility, rapid feedback cycles, and close collaboration with stakeholders during system development.This research focuses on the design and development of a web-based payroll information system tailored to the operational needs of the organization. The proposed system integrates employee data management, automated payroll calculations, and report generation into a single platform, enabling more efficient and accurate payroll processing. The implementation results demonstrate that the developed system significantly reduces processing time and improves data consistency in payroll management.System validation was conducted using the Black Box Testing method, comprising ten testing scenarios designed to evaluate the functional requirements of the system. The testing results indicate that all core system functionalities operate as expected and meet the predefined testing criteria. Overall, the proposed web-based payroll information system effectively enhances the efficiency and accuracy of payroll data processing and can serve as a practical solution for similar small- to medium-sized enterprises.